1991
DOI: 10.1007/bf00371817
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of patients with systemic sclerosis in Tokyo

Abstract: We conducted an epidemiological study of systemic sclerosis in the city of Tokyo using the records of patients who had been registered to receive free medical service for intractable diseases. A total of 636 patients were registered as having systemic sclerosis in 1987, and we sent questionnaires to the doctor of each patient. The contents of the questionnaires included the patient's name, sex, age, occupation, major symptoms, therapy and laboratory findings. We received 357 completed replies, and were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
45
3
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 9 publications
12
45
3
2
Order By: Relevance
“…In 120 patients, including all 9 patients with morphea, antinuclear antibody (ANA) test was performed using inch-rect immunofluorescence and double immunodiffusion methods, as previously described [7,8], Characteristics of SSc patients with and without morphea arc summarized in tabic I. That only 5 patients were male is consistent with the recent reports of a very low male to female ratio [9,10].…”
Section: Methodssupporting
confidence: 68%
“…In 120 patients, including all 9 patients with morphea, antinuclear antibody (ANA) test was performed using inch-rect immunofluorescence and double immunodiffusion methods, as previously described [7,8], Characteristics of SSc patients with and without morphea arc summarized in tabic I. That only 5 patients were male is consistent with the recent reports of a very low male to female ratio [9,10].…”
Section: Methodssupporting
confidence: 68%
“…However, we found a statistically significant increase in the percentage of males with SSc in our more recent cohort, from 3.9% (up to 1989) to 10.6% (from 1990 onward). Indeed, a previous Japanese study of SSc in patients with the onset before 1988 also showed a low percentage of males (6.4%, n = 636) [21]. This supports the hypothesis that the sex ratio of Japanese SSc patients has been changing recently with an increase in the number of male patients.…”
Section: Discussionmentioning
confidence: 52%
“…In England, the prevalence of SSc has been reported as 30.8 cases per million (based on 156 cases) (34), in Japan the prevalence estimate is 38 cases per million (based on 357 cases) (35), and in Iceland the prevalence estimate is 71 cases per million (based on 37 cases) (36). These studies included both limited and diffuse forms of SSc.…”
Section: Discussionmentioning
confidence: 99%